Sensitivity Analysis of The Financial Viability of Health Service Levy Rates Case Study: Construction of South Surabaya Regional General Hospital - Rachma Damayanti; Andi Patriadi; Sajiyo Sajiyo (Journal of Social Science, 2025)
This study aims to analyze the sensitivity of investment feasibility in the construction of South Surabaya Regional General Hospital using investment evaluation methods, namely Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The study also evaluated the sensitivity of the investment to changes in the health service retribution tariff as well as operational management costs. Primary and secondary data were collected to analyze the investment cash flow, which includes the initial investment cost, operational expenses, and revenue from the health service tariff. The results of the analysis show that the investment is feasible with positive NPV parameters, IRR greater than the minimum rate of return, and an investment payback period that is faster than the planned period. Sensitivity analysis revealed that the management cost component and revenue from service tariffs are the main factors affecting investment feasibility. Additionally, the study emphasizes the importance of strategic tariff adjustments and operational efficiency in ensuring the project's sustainability. The results of this study can be a valuable reference for the Surabaya City Government in making evidence-based policies related to hospital tariff optimization schemes and cost management.